Peran Perguruan Tinggi Dalam Menerapkan Pendidikan Anti Korupsi Sebagai Upaya Pencegahan Tindak Pidana Korupsi Di Kalangan Mahasiswa - Luh Juni Karini (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
This study aims to find out the workflow of acts of corruption, the various steps used to eradicate acts of corruption, and the important role of universities in helping reduce acts of corruption. In this study, the normative legal research method was used by carrying out studies through research on library materials and document studies. The results of the research show how the perpetrators committed acts of corruption and the course of their actions. The way a person commits an act of corruption is by means of a mode, or by taking turns. So to prevent this from happening, human beings in tertiary institutions, both students and lecturers, really need their role in preventing corruption. Besides that, the way to prevent acts of corruption is by implementing anti-corruption education, fostering an honest attitude as early as possible, the role of tertiary institutions is very important because universities are likened to vehicles that move to achieve goals with the right targets such as instilling an anti-corruption spirit in students.